INFORMAL DISPUTE RESOLUTION BASED ON ADAT LAW: A CASE STUDY OF LAND DISPUTE IN FLORES, EAST NUSA TENGGARA, INDONESIA - Sopian, Najmu Laila (Indonesia Law Review, 2015)
The issue of law enforcement is central to land property rights. Modes of property rights enforcement can be performed either with or without intervention of the state. This article focuses on the latter mode of enforcement; that is, how people manage to enforce their land rights without the involvement of state institutions and to what extent informal arrangements can offer effective enforcement and secure land property rights. This article also contributes to the debate on how formal and informal institutions can be used to secure property rights and resolve disputes over land ownership. In particular, this paper examines how the people of Flores, East Nusa Tenggara Province, settle land disputes among themselves. Many available studies indicate that the residents of Flores rely heavily on informal land dispute resolution based on adat (customary) law rather than formal or legal rules. Adat provides certain sense of security and has been proven effective in resolving conflicts in a relatively closed and homogeneous community. Moreover, it offers greater accessibility, flexibility and legitimacy that support reconciliation process between the disputing parties.